Pig sex determination using single-cell PCR for preimplatation genetic diagnosis - Fábián, Renáta; Pintér, Tímea; Magyar, Andrea; Bodó, Szilárd (Animal welfare, Ethology and Housing Systems (AWETH), 2018)
In the last decades productivity of pig breeding has increased significantly, due to the development and application of new reproductive technologies. Sex preselection of livestock progeny can be created by using preimplatation genetic diagnosis (PGD) and embryo transfer. After determining the sex of the blastomeres with a single-cell analysis obtained by embryo biopsy, the sexed embryos could be transfer into recipient females. The aim of our experiments was to develop a pig PGD from a single-cell obtained by embryo biopsy from in vitro produced embryos. In our study a duplex PCR for amplification of both sexes was applied. Two different specific primer sets were used, one as a positive control common to both sexes the pig mitochondrial 12S rRNA multicopy gene sequence and the other was a pig male-specific repeat sequence to detect the presence of Y chromosome. The PCR was developed using oocytes recovered from the ovaries to reach the necessary sensitivity of determine embryo sex from a single cell (6pg/μl DNA). The PCR products were easily distinguishable using agarose gel electrophoresis. At the samples originated from females a single band and at the males samples double bands were detectable. After the successful sets of the single-cell PCR as a method of PGD we biopsied 8-cell embryos, which were produced by in vitro fertilization and the sex of the embryos were determined.